Survey research methods - Fowler, Floyd J. 4 0 16; 5 (Los Angeles : Sage Publications, 2009)
Provides an overview of the survey research process, discussing the types of errors found in surveys, sampling, methods of data collection, survey interviewing, ethical issues, and other topics.
Includes bibliographical references and indexes.
Professional;Adult.
Keywords: 2 -- 0; 6; Social surveys. -- 20; 20; 2